2011
DOI: 10.1017/s0950268811000082
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antibiotic usage and susceptibility in nosocomial Enterobacteriaceae and Pseudomonas isolates following the introduction of ertapenem to hospital formulary

Abstract: There is concern that widespread usage of ertapenem may promote cross-resistance to other carbapenems. To analyse the impact that adding ertapenem to our hospital formulary had on usage of other broad-spectrum agents and on susceptibilities of nosocomial Enterobacteriaceae and Pseudomonas isolates, we performed interrupted time-series analyses to determine the change in linear trend in antibiotic usage and change in mean proportion and linear trend of susceptibility pre- (March 2004-June 2005) and post- (July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In a long-term study, despite an increasing use of ertapenem over a 9 year period, no association was found between ertapenem and changes in pseudomonal susceptibility to carbapenems [37]. Other studies have reported an increased susceptibility to imipenem among P. aeruginosa after introduction of ertapenem, presumptively due to decrease in group 2 carbapenems [35,36]. While the present study detected an overall decrease in carbapenem non-susceptible Pseudomonas isolates in the postintervention period, whether this is a direct impact of ertapenem or through indirect changes in other antimicrobials is unknown.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In a long-term study, despite an increasing use of ertapenem over a 9 year period, no association was found between ertapenem and changes in pseudomonal susceptibility to carbapenems [37]. Other studies have reported an increased susceptibility to imipenem among P. aeruginosa after introduction of ertapenem, presumptively due to decrease in group 2 carbapenems [35,36]. While the present study detected an overall decrease in carbapenem non-susceptible Pseudomonas isolates in the postintervention period, whether this is a direct impact of ertapenem or through indirect changes in other antimicrobials is unknown.…”
Section: Discussionmentioning
confidence: 84%
“…[35][36][37]. In many instances, these investigations reported improved susceptibilities of Enterobacteriaceae and Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been conducted in different US centres and around the world to evaluate whether introduction of ertapenem to hospital formularies has had an effect on the susceptibility of Gram-negative bacteria to carbapenems and other antibiotics [6][7][8][9][10][11][12][14][15][16]. The studies typically focused on the number of defined daily doses (DDD) of antibiotic used and changes in the susceptibility of P. aeruginosa and, in some cases, Enterobacteriaceae, before and after ertapenem formulary introduction.…”
Section: Ecological Evidence From Clinical Studiesmentioning
confidence: 99%
“…Multiple single-centre and multicentre ecological studies have recently been conducted that explore whether ertapenem has an impact on hospital ecology [6][7][8][9][10][11][12][13][14][15][16]. Sufficient long-term data are now available to examine whether ertapenem use has resulted in a change in the proportion of carbapenem-susceptible Pseudomonas or in other associated changes in susceptibility to carbapenems.…”
Section: Introductionmentioning
confidence: 99%